Intelligent Systems Technologies and Applications Volume 1 - Berretti, Stefano; Thampi, Sabu M.; Srivastava, Praveen Ranjan (Advances in Intelligent Systems and Computing, 2016)
This book contains a selection of refereed and revised papers of Intelligent Techniques and Applications track, and the Special Track on Intelligent Image Processing and Artificial Vision track originally presented at the International Symposium on Intelligent Systems Technologies and Applications (ISTA), August 10-13, 2015, Kochi, India.  .